Factors Affecting Health-Promoting Lifestyles Among Community Residents at East Gyogone Ward, Insein Township - Meemee, Rita; Khin, Naw Ohn Khin; Aung, Min Htike (UI Scholars Hub, 2021)
Background: Non-communicable diseases (NCDs) are becoming major challenges for health professionals. Health-promoting lifestyles (HPL) are one of the main criteria for determining health and recognized as the main factor affecting the development of chronic NCDs. This study aimed to determine factors affecting HPL practices among community residents. Methods: A cross-sectional descriptive study was conducted in Insein Township, Yangon, Myanmar. A total of 194 participants were recruited by using systematic sampling method, and self-administered questionnaires for sociodemographic characteristics and Health-Promoting Lifestyle Profile II were used for data collection. Independent sample t-test and one-way analysis of variance were employed in the data analysis. Results: The overall mean score for HPL was 126.67 ± 21.29. The participants performed best in the spiritual growth subscale (25.1 ± 5.08) but worst in the physical activity subscale (14.23 ± 4.46). More than half (56.70%) of them had moderate HPL level. Participants’ HPL showed significant associations with education level, occupation, total family income per month, perception of health status, smoking, and drinking alcohol status (p < 0.05). Conclusions: This study highlights the needs for redesigning health promotion programs to increase awareness of community residents on HPL, to empower them in developing HPL, and to apply them in their everyday lives.